Fractional CO2 Laser for Treatment of Female Stress Urinary Incontinence - hameed, shawnm majeed; Saeed, Nadia M.; Muhaibis, Baraa M. (Iraqi Journal of Laser, 2021)
Background: Urinary incontinence (UI) is a common disorder that affects women of various ages and impacts all aspects of life. This condition negatively influences quality of life. Fractional CO2 laser (10600nm) is the recent method for treatment of stress urinary incontinence in women. Objectives: The purpose of the study was to evaluate the efficacy and safety of fractional CO2 laser (10600nm) in the treatment of female stress urinary incontinence. Materials & Methods: This study was done from July 2020 to February 2021conducted at the laser institute for postgraduate studies university of Baghdad, patients collected from a private clinic and the Department of Obstetrics and Gynecology of Al-Kadhimiya private hospital, Baghdad, Iraq. Twenty women clinically diagnosed with SUI preferring non-surgical treatment were recruited to the study, their mean ages 43.6 + 13.9 years. Response to treatment was assessed at baseline and at one month follow up after the third session using a pelvic Floor Questionnaire (PFQ-UI).The laser parameters used were CO2 laser wavelength 10600 nm, power 35 watt, duration 1.0 ms, distance 1.0 mm, scan mode normal, scan times 4 and scan Rows 4,Interval 0.5s. Results: Most of the twenty women included in the study 80 % reported satisfaction and 20% not satisfied with treatment after 3 sessions of CO2 laser four weeks apart. Conclusion: Fractional CO2 laser treatment is an easy to use, minimally invasive and effective option for treatment of SUI.